Alqur’an Reading Quality of The Santri : An Experimental Study Toward the Usage of An-Nahdliyah Method - M Kharis Fadillah (Journal of Research in Islamic Education, 2019)
An-Nahdliyah is one method that is widely used for Ustadz and Uztadzah in teaching reading the Qur'an. The purpose of this study is to compare the quality of santri reading with the An-Nahdliyah method which uses beats and does not use beats. The approach in this study is a quantitative approach. The population in this study amounted to 401 santri. The sample is 40 santri. Data collection techniques are, tests, observation, documentation, interviews. Strengthening measuring instruments using Test Validity, Reliability Test. And data analysis techniques using Data Normality Test, Homogeneity Test and Hypothesis Test. Based on the results of the research and discussion, the following conclusions were obtained: 1) The quality of reading by santri Madrasah Diniyah Tarbiyatul Athfal with the An Nahdliyah method that uses beats is included in the good category. 2) The quality of the reading of the students of Madrasah Diniyah Nurussalam with the An Nahdliyah method that does not use beats is included in the good category. 3) There are differences in the quality of the santri's reading by using beats and not using beats on the students of Madrasah Diniyah Tarbiyatul Athfal and Madrasah Diniyah Nurussalam students